The Influence of Leadership and Conflict on Employee Performance - Firdaus, Muhammad Aziz; Rinda, Rachmatulaily Tinakartika; Megawati, Dewi; Rahmawati, Rika (prodima@fe.uika-bogor.ac.id, 2024)
This research was conducted at PT Sonoco Indonesia, performance is the result of quality and quantity of work achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Performance is influenced by factors including leadership and conflict. In this study, what will be discussed is the Influence of Leadership and Conlic on Employee Performance. The population of this study is employees of PT. Sonoco Indonesia, so that the total population in this study is 150 employees. The sampling method used in this study is probability sampling based on stratified random sampling, so that a sample of 57 employees was obtained. Based on the results of the study, it can be concluded that leadership has a positive influence on employee performance, the relationship of leadership strength and conflict on employee satisfaction of PT. Sonoco Indonesia Value r = 0.822 this shows that the relationship between the variables Leadership and (X1) Conflict(X2) and Y (Performance) is very strong and positive with a determination coefficient result of 0.663 or 66.3%. The results of regression analysis Y = 4.546 +0.847 X1 + 0.047 X2 and F test Partial hypothesis with t count = 56.064 > F table = 3.17, then Ho was rejected (Ha was accepted), meaning that there was a significant influence between leadership and conflict on performance Respondents' perception of performance (Y).